Impact of the noise spikes on sequential symbol synchronizers - Reis, António D. (2009)
This work study the impact of the noise spikes on sequential symbol synchronizers. We distinguish two synchronizers variants which are: the one that processes the both data transitions and the one thatprocess only the positive data transition. In each one, weconsider two versions namely the manual and the automatic. The objective is to study the various synchronizers outputjitter UIRMS (Unit Interval Root Mean Square) versus theinput SNR (Signal to Noise Ratio).